2022
DOI: 10.1109/jsen.2022.3207213
|View full text |Cite
|
Sign up to set email alerts
|

A New Platform of Iron Oxide-Based Nanoparticles Assay Using GMR Chip-Based Sensor With Microcontroller

Abstract: The low-cost, simple, and fast quantitative assay of magnetic nanoparticles (MNPs) is important for the development of magnetic-based immunoassay applications. However, the bulky sensing element and instruments of the recent iron oxide-based MNPs assays are still concerns that should be resolved. This article reports the new platform of an iron oxide-based MNPs label assay using the commercial giant magnetoresistance (GMR) chip AAL024, manufactured by Nonvolatile Electronics (NVE) Corporation, complemented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…84 Wibowo, et al suggested using an OA circuit with LM 358 as a basic differential amplifier to overcome the small output voltage of the MR chip. 40,85 OA ICs offer output voltage amplification circuit design freedom due to their high voltage gain (up to 100 dB). A differential amplifier suppresses simultaneous input voltages to increase the difference between two input voltages.…”
Section: Working Principle Of Boc Based On the Tmr/ionps Coupled Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…84 Wibowo, et al suggested using an OA circuit with LM 358 as a basic differential amplifier to overcome the small output voltage of the MR chip. 40,85 OA ICs offer output voltage amplification circuit design freedom due to their high voltage gain (up to 100 dB). A differential amplifier suppresses simultaneous input voltages to increase the difference between two input voltages.…”
Section: Working Principle Of Boc Based On the Tmr/ionps Coupled Sensorsmentioning
confidence: 99%
“…Numerous studies have been undertaken on this topic. 41,51,85,87,88 Wibowo, et al proposed the quantification method of silver-coated magnetite using a GMR chip manufactured by NVE Corp. 85 By using a similar chip, Ardiyanti, et al perform the successful quantification of GSmagnetite and streptavidin-coated MNPs. 41 Each research reveals the linear dependence of the sensor signal to the MNPs amount with the sensitivity in the order of mV/mg/mL.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Their low output voltage requires expensive and heavy voltage meters, which restricts their availability and portability. At the same time, we also introduced a new platform for traditional chemical and green synthesis-based MNPs testing using only single-chip combined with a microprocessor and an amplifier circuit, producing a consistent and real-time signal [13,14].…”
Section: Introductionmentioning
confidence: 99%